Latin in internet memes: new communicative function - Михайлова, Олена Григорівна (Київський національний університет імені Тараса Шевченка, 2019)
The article is devoted to the research of Internet memes as universally precedential cultural phenomena, to determining Latin special role in the construction and functioning of virtual memes. Latin Internet memes are considered as emotionally colored units of cultural information the first source of which are different elements of the knowledge of Latin that are copied and disseminated among Internet users during communication as a text (inscription, reference) or as a text and an icon part (drawing, photo, table). On the base of new virtual units of communication the functions of memes in Internet communication were determined, in particular: game, representative, communicative, phatic, integrative, affective. Local Latin Internet memes served as the material for the research placed on English sites “Classic Latin Memes”, “Dank Latin Memes”, as well as on Russian site “Latine masculino”. Dead Latin within Internet memes renews its communicative function and gains more popularity in the Internet space thanks to its perception as “prestigious” language of communication. By style the majority of Latin Internet memes are ironically marked and motivating, though demotivating memes are also possible. The goal of motivating memes is “to revive”, modernize archaic Latin and make it more accessible and attractive in order to encourage the focus audience to study it. Internet communication via memes’ mediation represents complex mental processes, when the user has not only to perceive a background picture and decode (translate) Latin text, but also to comprehend cultural connotations and associative links which result in comic effect during memes’ perception. The research of Latin Internet memes in pragmatic, communicative and cognitive aspects is of positive perspective both from synchronic and diachronic points of view, since it presents new opportunities for the study of modern evolutionary processes in the history of ancient language, reveals a mechanism of decoding cultural information, contributes to the development of Internet linguistics.

Стаття присвячена дослідженню Інтернет-мемів як універсально-прецедентних культурних феноменів, визначенню особливої ролі латинської мови у створенні та функціонуванні віртуальних мемів. Латинські Інтернет-меми розглядаються як емотивно забарвлені одиниці культурної інформації, першоджерелом якої є різнорівневі елементи знання латинської мови, що копіюються і поширюються серед Інтернет-користувачів у вигляді тексту (напис, підпис) або тексту та іконічної частини (малюнок, фото, таблиця) у процесі комунікації. На прикладі нових віртуальних одиниць спілкування визначено функції мемів в умовах Інтернет-комунікації, а саме: ігрову, репрезентативну, комунікативну, фатичну, інтеграційну, афективну. Матеріалом дослідження слугували локальні латинські Інтернет-меми, представлені на англомовних сайтах «Classic Latin Memes» «Dank Latin Memes», а також російськомовному сайті «Latine masculinо». В Інтернет-мемах «мертва» латина відновлює комунікативну функцію і набуває популярності у віртуальному просторі через позитивне сприйняття її як «престижної» мови спілкування. Стиль більшості латинських Інтернет-мемів є іронічно-мотивуючим, хоча можливі також меми-демотиватори. Мета мотивуючих мемів – «оживити», осучаснити архаїчну латину, зробити її більш доступною і креативною, заохотити до її вивчення. Інтернет-комунікація через посередництво мемів передбачає складні ментальні процеси, коли користувач має не тільки сприйняти картинку-фон і перекласти латинський текст, але також зрозуміти культурні конотації і асоціативні зв’язки, що породжують комічний ефект під час сприйняття мема. Дослідження латинських Інтернет-мемів у прагматичному, комунікативному і когнітивному аспектах є перспективним як з точки зору синхронії, так і діахронії, оскільки надає нові можливості для вивчення сучасних еволюційних процесів в історії давньої мови, розкриває механізм декодування культурної інформації, сприяє подальшому розвитку інтернет-лінгвістики.
Латинська мова в інтернет-мемах: нова комунікативна функція
Keywords: Internet communication; meme; Internet meme; Latin; Інтернет-комунікація; мем; Інтернет-мем; латинська мова